(untitled) (Journal of the College of Basic Education, 2022)
The research included studying the effect of some of the new Schiff base compounds on the activity of the cholinesterase enzyme in human blood serum. It was observed that the used compounds cause activation of the enzyme activity. Using different concentrations of these compounds and studying the type of inhibition. The results obtained from the weaver Burk line showed that the inhibition is non-competitive and was The percentage of inhibition with these compounds ranged between (39.44-87.16)%.